Ringkasan Penelitian Kebutuhan Jabatan Fungsional Di Lingkungan Kementerian Perhubungan - Kuswati, Atik S (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Policies and strategies fur Jmman rewurce derelopment in tranSfX»1ation kior is une of effurt to enhanceEerVices. Therefore, generate quality human resources and professional. is needed in aarmiance with theirfu:nctiona1 fXJSitions. Balancing quality and quantity of lmman resources with advance tranSJXJrl technologiesare exprted that transrxJrlation grnls will. re more sucressfa1 as 'lIBll as CXJr11¢e lXJth within and other amtries.Aavrding to improving transp:Jrlation sifthJ rxJlicy is net:ES.'m1j to cklxdap fafhJ audit amcept in prerentioneJjUrts to reduce tk incidence and accidents. Related tk mse is needed functional. fXJSitions as a sup;rvifm/insp?Cfor/auditor of each f£dmical. institution in ministnj of transp:Jrlation !£Cior (diredorale genem1. land trans]XJrl, mil'UXlljS, f£ll and air). Sup?YViror assi.gned to guarantee tk jaslbilittj of transp:Jrlation foci1itX!s indudingritk analysis of ead1 violation of eligibility requirements.Functional. J standards is necessary b:cauf£ it is a CUfXlbility that is lxlsed on knowledge, skills andgcxxl attitude whidi refers to tk peformance required This matter is explained in tk study of tk nea:ssity offuncional position by research and developmen of ministry of transport on 2009.